2022
DOI: 10.1186/s12891-022-05858-w
|View full text |Cite
|
Sign up to set email alerts
|

Plantar and dorsal approaches for excision of morton’s neuroma: a comparison study

Abstract: Background Morton’s neuroma is a painful enlargement of the plantar digital nerve between the metatarsal heads that causes pain of the forefoot. Several approaches have been used to treat Morton’s neuroma, each of them having distinct advantages and disadvantages. Objectives The purpose of this study was to investigate and compare the clinical outcomes of neurectomy in the treatment of Morton’s neuroma through plantar and dorsal approaches. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 25 publications
0
11
0
2
Order By: Relevance
“…The results showed that there was a statistically significant difference in the occurrence of scar issues between PG and DG (OR, 2.90[95%CI, 1.40 to 5.98]; p = 0.004). Comparison of sensory loss(bothersome) between PG and DGAs shown in Fig. 3c, three studies [6, 12, 22], including 140 feet (PG, 70 feet; DG, 70 feet), revealed loss of sensation, which is bothersome. It was selected to employ the fixed effect model ( p = 0.43, I 2 = 0%).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…The results showed that there was a statistically significant difference in the occurrence of scar issues between PG and DG (OR, 2.90[95%CI, 1.40 to 5.98]; p = 0.004). Comparison of sensory loss(bothersome) between PG and DGAs shown in Fig. 3c, three studies [6, 12, 22], including 140 feet (PG, 70 feet; DG, 70 feet), revealed loss of sensation, which is bothersome. It was selected to employ the fixed effect model ( p = 0.43, I 2 = 0%).…”
Section: Resultsmentioning
confidence: 98%
“…The second one [20] utilized the 36-Item Short Form Health Survey (SF-36) and the Foot Function Index (FFI) for comparison, but they did not take complications into account. Five studies [6,12,[21][22][23] ultimately satisfied our eligibility requirements, and the flow chart of the selected literature is shown in Fig. 1.…”
Section: Literature Search Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…One study comparing outcomes following plantar versus dorsal approaches for recurrent Morton neuroma found no significant difference in postoperative patient outcomes. That study suggested that surgeons utilize the approach with which they are most comfortable 12 . Gould et al reported an 85% success rate with collagen conduit, which was similar to if not slightly improved compared with the other prior studies.…”
mentioning
confidence: 99%